2018
DOI: 10.5817/di2018-2-27
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Analysis of Interpersonal Metadiscourse Markers in Persuasive Local Newspaper Articles

Abstract: This paper aims to explore the role interpersonal metadiscourse markers play in theconstruction and achievement of persuasion in local British and Iranian newspapers.To this end, a corpus of 120 persuasive opinion articles published in two local Iraniannewspapers, namely Isfahan Ziba and Isfahan (Emrooz) Today, and two local Britishnewspapers, namely Liverpool Echo and Chronicle Live, from July 2015 to June 2016,were randomly selected and analyzed based on Dafouz-Milne’s (2008) taxonomy ofinterpersonal metadis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Apart from that, Bedu's ( 2019) study revealed that the use of attitude markers expressed the writers' affective attitudes in conveying surprise, obligation, agreement, and importance in the text. This ascertains that attitude markers are persuasive devices whose function is to express writers' affective values toward propositional content as they are applied differently in text (Farnia & Mohammadi, 2018). The use of commentaries in creating rapport with the readers is supported in the study of Hashemi and Golparvar (2012), where they concurred that commentaries were used to establish the interaction between the writer and the readers.…”
Section: Discussionmentioning
confidence: 84%
“…Apart from that, Bedu's ( 2019) study revealed that the use of attitude markers expressed the writers' affective attitudes in conveying surprise, obligation, agreement, and importance in the text. This ascertains that attitude markers are persuasive devices whose function is to express writers' affective values toward propositional content as they are applied differently in text (Farnia & Mohammadi, 2018). The use of commentaries in creating rapport with the readers is supported in the study of Hashemi and Golparvar (2012), where they concurred that commentaries were used to establish the interaction between the writer and the readers.…”
Section: Discussionmentioning
confidence: 84%
“…To date, studies on metadiscourse that focused on news were not on business news, but they were on newspaper discourse. Farnia and Mohammadi (2018) in their study on opinion articles demonstrated that interpersonal metadiscourse was present in both British and Iranian newspapers, but they only focused on the role of interpersonal metadiscourse in the newspapers. This could be a drawback in Farnia and Mohammadi's (2018) study because textual metadiscourse is important for examination as it makes the text more lucid and cogent.…”
Section: Introductionmentioning
confidence: 99%
“…Farnia and Mohammadi (2018) in their study on opinion articles demonstrated that interpersonal metadiscourse was present in both British and Iranian newspapers, but they only focused on the role of interpersonal metadiscourse in the newspapers. This could be a drawback in Farnia and Mohammadi's (2018) study because textual metadiscourse is important for examination as it makes the text more lucid and cogent. Mardani's (2017) study on newspaper articles suggested that metadiscourse had a very significant role in persuasive texts in both writing and translating in newspaper articles.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar view, research in academic writing has long established that functional metadiscourse plays an essential role in academic writing, owning to different communicative functions (Farnia & Mohammadi, 2019;Ho & Li, 2018;Hong & Cao, 2014;Hyland, 2005aHyland, , 2010Hyland & Tse, 2004;Kim & Lim, 2013;Lee & Deakin, 2016;Li & Wharton, 2012;Mur-Duenas, 2011;Musa et al, 2019). Thus, as a way to understand the functional metadiscourse in negotiating meanings in a text and establishing a connection with readers of a text, our previous study (Lo et al, 2020) examined the use of metadiscourse in academic writing across four areas of study in education.…”
Section: Introductionmentioning
confidence: 99%